Norbornadiene-bridged diarylethenes and their conversion into turn-off fluorescent photoswitches - Büllmann, Simon; Jäschke, Andres (Chemical communications, 2020)
We describe the synthesis and characterization of novel diarylethene photoswitches that contain a norbornadiene bridge and operate as p-type positive photochromes. One of the double bonds of norbornadiene is furthermore utilized to attach a fluoresceine tetrazine by an iEDDA cascade reaction, thereby forming a turn-off mode fluorescent photoswitch.
Gesehen am 27.07.2020